2006
DOI: 10.1182/blood-2005-10-4020
|View full text |Cite
|
Sign up to set email alerts
|

Complex interaction of BCRP/ABCG2 and imatinib in BCR-ABL–expressing cells: BCRP-mediated resistance to imatinib is attenuated by imatinib-induced reduction of BCRP expression

Abstract: Imatinib, a potent tyrosine kinase inhibitor, is effluxed from cells by the breast cancer resistance protein (BCRP/ABCG2), yet published studies to date fail to demonstrate resistance to imatinib cytotoxicity in BCRP-overexpressing cells in vitro. We investigated cellular resistance to imatinib in BCR-ABL-expressing cells transduced and selected to overexpress BCRP (K562/BCRP-MX10). These cells exhibited a 2-to 3-fold increase in resistance to imatinib (P < .05) and a 7-to 12-fold increase in resistance to mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 30 publications
(41 reference statements)
9
98
0
Order By: Relevance
“…Interestingly, however, imatinib decreased the expression of BCRP only in K562/BCRP-MX10 cells expressing BCR-ABL, but not in cells lacking BCR-ABL expression. The underlying mechanism for these differential responses involved downstream effects of imatinib inhibition of BCR-ABL, leading to the decreased phosphorylation of Akt, subsequently leading to reduced BCRP expression (Nakanishi et al, 2006). This study showed that an active PI3K -Akt pathway is responsible, at least in part, for maintenance of BCRP expression (Figure 1).…”
Section: Imatinibmentioning
confidence: 84%
See 2 more Smart Citations
“…Interestingly, however, imatinib decreased the expression of BCRP only in K562/BCRP-MX10 cells expressing BCR-ABL, but not in cells lacking BCR-ABL expression. The underlying mechanism for these differential responses involved downstream effects of imatinib inhibition of BCR-ABL, leading to the decreased phosphorylation of Akt, subsequently leading to reduced BCRP expression (Nakanishi et al, 2006). This study showed that an active PI3K -Akt pathway is responsible, at least in part, for maintenance of BCRP expression (Figure 1).…”
Section: Imatinibmentioning
confidence: 84%
“…Also HEK293 cells transfected with BCRP variants, both wild-type (Arg at position 482, HEK293/R) and mutants (Gly or Thr at position 482, HEK293/G and HEK293/T), showed a markedly decreased imatinib accumulation, which could almost be completely reversed by the BCRP-specific inhibitor Ko143 (Burger et al, 2004). Also the specific BCRP inhibitor fumitremorgin C (FTC) could reverse the two-to three-fold resistance to imatinib of BCR-ABL-expressing cells transduced and selected to overexpress BCRP (K562/BCRP-MX10) (Nakanishi et al, 2006). Moreover, Brendel et al (2007) postulated that imatinib is a BCRP substrate based on the observations that (a) BCRP-transduced K562 cells were two-to three-fold resistant to imatinib-induced apoptosis and that inhibition of BCRP with FTC completely abrogated the resistant phenotype, (b) imatinib directly interacts with BCRP at the substrate binding site and stimulates BCRP ATPase activity, and finally (c) BCRP-transduced cells displayed significantly less imatinib accumulation.…”
Section: Imatinibmentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 Moreover, both transporters show elevated expression in CML stem cells, 52,53 and several known SNPs modify 56 Although they did not investigate the relationship between the tested SNPs and plasma IM concentration, the authors noted that interindividual variation in hepatic IM uptake and clearance could lead to changes in systemic IM concentration. Our results should be interpreted within the context of the study limitations, which primarily involve the sample size of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies showed that growth signaling pathways also affect ABCG2 expression. The inhibition of PI3K/Akt signaling in leukemia cells causes a downregulation of total ABCG2 expression (12). In hepatocellular carcinomas, a triterpene in fruits and vegetables has been found to suppress the self-renewal ability of CSCs and to enhance the effect of chemotherapeutic agents through the PTEN/Akt/ ABCG2 pathway (13).…”
Section: Introductionmentioning
confidence: 99%